Differences in Peripheral and Tissue Immune Cell Populations Following Haematopoietic Stem Cell Transplantation in Crohn's Disease Patients. (6th December 2018) - Corraliza, Ana M; Ricart, Elena; López-García, Alicia; Carme Masamunt, Maria; Veny, Marisol; Esteller, Miriam; Mayorgas, Aida; Le Bourhis, Lionel; Allez, Matthieu; Planell, Núria; Visvanathan, Sudha; Baum, Patrick; et al.
Abstract: Background and Aims: Recent studies have shown the efficacy of autologous haematopoietic stem cell transplantation [HSCT] in severely refractory Crohn's disease [CD] patients. HSCT is thought to eliminate auto-reactive cells; however, no specific studies of immune reconstitution in CD patients are available. Methods: We followed a group of CD patients [ n = 18] receiving autologous HSCT, with 50% of them achieving endoscopic drug-free remission. To elucidate the mechanisms driving efficacy, we monitored changes after HSCT in blood and intestine immune-cell composition. CD patients [ n = 22] receiving anti-tumour necrosis factor [TNF]-α were included for comparison. Results: Severe immune ablation followed by HSCT induced dramatic changes in both peripheral blood T and B cells in all patients regardless of the efficacy of the treatment. Endoscopic remission at week 52 following HSCT was associated with significant intestinal transcriptional changes. A comparison of the remission signature with that of anti-TNFα identified both common and unique genes in the HSCT-induced response. Based on deconvolution analysis of intestinal biopsy transcriptome data, we show that response to HSCT, but not to anti-TNFα, is associated with an expansion of naïve B-cells, as seen in blood, and a decrease in the memory resting T-cell content. As expected, endoscopic remission, in response to both HSCT and anti-TNFα, led to a significant reduction in intestinal neutrophil and M1 macrophage content. Conclusions: Peripheral blood immune remodelling after HSCT does not predict efficacy. In contrast, a profound intestinal T-cell depletion that is maintained long after transplant is associated with mucosal healing following HSCT, but not anti-TNFα.